2021
DOI: 10.3390/geosciences11100422
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires Effect on Debris Flow Occurrence in Italian Western Alps: Preliminary Considerations to Refine Debris Flow Early Warnings System Criteria

Abstract: Rarely, a close correlation between wildfires and the occurrence of channelized debris flows has been observed in the Western Italian Alps. Only two cases in history have been reported, after brief and localized rainfall events of moderate intensity in Italy's Piemonte region (NW Italy) caused debris flows, on 18 July 2005, in Verbania province (Pallanzeno municipality), and on June 2018 in Turin province (Bussoleno municipality). These phenomena occurred after a large portion of the catchments were affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…As previously disclosed, the landslide and wildfire density heatmaps do not show a high correlation. According to [22], in the Western Alps, a close correlation has been found for debris flow events in small alpine catchments that were previously affected by wildfires. However, the correlation of the shallow landslides with wildfires is verified only for some local cases in the Biella and Verbano provinces (north Piemonte) and Lanzo valleys (north-western Piemonte).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As previously disclosed, the landslide and wildfire density heatmaps do not show a high correlation. According to [22], in the Western Alps, a close correlation has been found for debris flow events in small alpine catchments that were previously affected by wildfires. However, the correlation of the shallow landslides with wildfires is verified only for some local cases in the Biella and Verbano provinces (north Piemonte) and Lanzo valleys (north-western Piemonte).…”
Section: Resultsmentioning
confidence: 95%
“…In the investigated area, wildfire occurrence also plays a remarkable role in modifying the slopes' surficial characteristics. The effect of wildfires on slope stability is highlighted by many authors [19][20][21][22]. All cited works draw attention to the need for integrating post-fire hazard into shallow landslide prediction systems and, in broader terms, into risk mitigation studies.…”
Section: Study Areamentioning
confidence: 99%
“…It has been demonstrated that the area ratio of outcropping bedrock vs. plant cover, and consequently the capacity of a catchment to generate debris flow, is https://doi.org/10.1051/e3sconf/202341503030 , 03030 (2023) E3S Web of Conferences 415 DFHM8 strongly influenced by the occurrence of wildfires that largely involve a given catchment [4]. In that case, the debris flows' triggering thresholds should be lowered from 20% to 60% compared with the standard values in Tab.…”
Section: Figmentioning
confidence: 99%
“…In addition, reduced protective ground cover, lack of vegetation canopy [17], changes in soil properties [21], decreased infiltration and increased runoff [1,17,22] can intensify erosion processes. Moreover, other landscape characteristics, beyond the fire, can influence debris flow generation and mass movement, including geological attributes [23], or the presence of fine-grained material [24,25]. Despite their significance and frequency, there is no systematic diagnosis of debris flow risks after forest fires in the Mediterranean region [26].…”
Section: Introductionmentioning
confidence: 99%